2017
DOI: 10.5897/ajb2017.16168
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of virus isolates from genus Potyvirus infecting Vigna subterranea in Burkina Faso

Abstract: Bambara groundnut (Vigna subterranea) is an African legume with a great nutritional, economic and social potential. However, one of the main constraints to this crop is viral diseases which reduced yields. Indeed, approximately 12 viruses have been reported to infect bambara groundnut. Among these, only four were reported from Burkina Faso, namely, cowpea aphid-borne mosaic virus (CABMV), bean common mosaic virus strain-blackeye cowpea mosaic (BCMV-BlCM), peanut mottle virus (PeMoV), and cowpea mottle virus (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…In both nucleotide and protein based phylogenetic trees, group 1 isolates clustered with CABMV isolates only. Notably, this CABMV group included also two isolates (MF277031 and MF277034) recently characterized from Bambara groundnut in Burkina Faso [4]. Group 2 and group 3 formed two new clusters which did not include any already known virus isolate.…”
Section: Phylogenetic Diversity Of Bambara Groundnut Potyvirusesmentioning
confidence: 89%
See 4 more Smart Citations
“…In both nucleotide and protein based phylogenetic trees, group 1 isolates clustered with CABMV isolates only. Notably, this CABMV group included also two isolates (MF277031 and MF277034) recently characterized from Bambara groundnut in Burkina Faso [4]. Group 2 and group 3 formed two new clusters which did not include any already known virus isolate.…”
Section: Phylogenetic Diversity Of Bambara Groundnut Potyvirusesmentioning
confidence: 89%
“…Viruses of the genus Potyvirus were clearly detected by RT-PCR from field samples of Bambara groundnut using widely used potyvirus universal primers [4] [9] [14] [15]. In addition, sequencing of the CP gene and sequence analysis confirmed that virus isolates belonged to the genus Potyvirus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations